Effect of methyl jasmonate and sucrose on endogenous non-structural carbohydrates in petals and leaves of cut ‘First Red’ roses (Rosa hybrida L.) - Terry, Leon A.; Foukaraki, Sofia G.; Cook, Balwinder; Papadimitriou, Michael D. (Islamic Azad University, 2017)
Effects of exogenously applied methyl jasmonate (MeJA) and sucrose on vase life and non-structural carbohydrate concentration in petals and leaves of cut ‘First Red’ roses were investigated. Roses were placed in sealed plastic containers and received MeJA vapour treatment (0.1 μL MeJA L-1) for 24 h at 20°C. Flowers were then placed in individual bottles containing 0 or 2% (v/v) sucrose solution. Flower petals and the two uppermost five-leaflet leaves were detached on days 0, d 5 and d 10 of vase life. Samples were individually snap-frozen in liquid nitrogen and freeze-dried. Non-structural carbohydrates were extracted and quantified using standard HPLC coupled to evaporative light scattering detection. The MeJA vapour treatment enhanced vase life of flower and foliage of ‘First Red’ roses. Significant differences were observed between foliage life of cut ‘First Red’ roses that were treated with MeJA and sucrose, but not for flower life. Rose stems treated with MeJA in the absence of sucrose had an extended vase life compared to roses treated with 2% sucrose alone (14.0 vs. 12.8 days of vase life). Sucrose and myo-inositol, and to a lesser extent glucose concentrations in petals of cut roses decreased during vase life, even when flowers were supplied with 2% sucrose. Concomitant to this, fructose levels in petals increased during vase life. Neither sucrose nor MeJA had a significant effect on any of the sugars measured in petals of cut roses. In contrast, significant differences were apparent for all sugars measured in leaves that were treated with MeJA and sucrose solutions. The combination of MeJA and 2% sucrose solution sharply increased endogenous sucrose concentration in leaves, but the opposite was shown in the absence of 2% sucrose. Sucrose treatment alone did not consistently alter endogenous sucrose concentration. Interactions between MeJA and sucrose on sugar metabolism are discussed.
Keywords: Fructose; Glucose; Myo-inositol; Rosa hybrida L; Sucrose